2007
DOI: 10.1186/1471-2334-7-74
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of tuberculosis in an Indian population by an indirect ELISA protocol based on detection of Antigen 85 complex: a prospective cohort study

Abstract: Background: Diagnosis of tuberculosis (TB) remains problematic despite many new advanced diagnostic methods. A reliable and rapid diagnostic test, which could be performed in any standard pathology laboratory, would help to obtain definitive early diagnoses of TB. In the present study we describe a prospective evaluation for demonstrating Antigen (Ag) 85 complex in the sera from TB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 20 publications
2
52
0
Order By: Relevance
“…A monoclonal antibody was also generated against the Ag85c and the antigen was found in the sputum of patients with PTB (Wallis et al 1998) and in patients with EPTB. A study performed using cerebrospinal fluid indicated that an indirect ELISA test using monoclonal antibodies against the Ag85c yielded 82% sensitivity and 86% specificity (Kashyap et al 2007). In this study, the Ag85c test (Ag85c) reached 85% sensitivity and 77.5% specificity and the Ag85A peptide tests achieved better sensitivity and specificity when compared to Ag85c: peptides 11005 and 11006 had a sensitivity of 98.3% for the EPTB group and peptide 29878 exhibited specificities of 97.4% and 96.4%, for the PTB and EPTB groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A monoclonal antibody was also generated against the Ag85c and the antigen was found in the sputum of patients with PTB (Wallis et al 1998) and in patients with EPTB. A study performed using cerebrospinal fluid indicated that an indirect ELISA test using monoclonal antibodies against the Ag85c yielded 82% sensitivity and 86% specificity (Kashyap et al 2007). In this study, the Ag85c test (Ag85c) reached 85% sensitivity and 77.5% specificity and the Ag85A peptide tests achieved better sensitivity and specificity when compared to Ag85c: peptides 11005 and 11006 had a sensitivity of 98.3% for the EPTB group and peptide 29878 exhibited specificities of 97.4% and 96.4%, for the PTB and EPTB groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously in the year 2007, monoclonal antibodies against antigen 85 complex have been used for serodiagnosis by indirect ELISA method [16]. LED based fluorescence microscopy has been reported to be 10% more sensitive than ZN microscopy [16].…”
Section: Proteins Released By M Tb Bacilli During Growthmentioning
confidence: 99%
“…LED based fluorescence microscopy has been reported to be 10% more sensitive than ZN microscopy [16]. The transformation in TB diagnosis was brought about with the introduction of Genexpert test, which diagnoses TB by detecting the presence of TB bacteria, as well as testing for resistance to the drug Rifampicin [17].…”
Section: Proteins Released By M Tb Bacilli During Growthmentioning
confidence: 99%
“…Antigen85 complex and CFP M. tuberculosis elicits detectable IgG response in tuberculosis patients. Sensitivity and specificity of assays utilizing Ag85 complex have been reported to range from 82-84.1% and 85.2-86% respectively [8]. Serological tests detecting IgG antibody against CFP showed sensitivity and specificity of 60.4 to 66% and 73.8 to 85.2% respectively [9][10][11].…”
Section: Introductionmentioning
confidence: 99%